Analysis of The Application of Life Cycle Cost Method of Green Retrofit of Mosque Building Based on GBCI and EDGE Benchmarks to Improve Investment Performancej - Agnes Purba; Yusuf Latief (Jurnal Indonesia Sosial Teknologi, 2024)
This study conducts a comprehensive life cycle cost analysis (LCC) of green retrofitting in mosque buildings, assessing its financial feasibility and performance. The research involves a risk assessment of three crucial stages: pre-, construction, and post-construction. A Likert scale is employed for the validation process based on responses from 51 experts involved in green building retrofit projects. Results indicate that the highest risk occurs during construction, impacting investment performance. Sensitivity analysis reveals the potential longevity of investments, with pre-construction risks affecting the Net Present Value (NPV) in the 18th year and post-construction risks proving feasible by the 17th year. The study introduces benchmarks such as NPV, Internal Rate of Return (IRR), Benefit-Cost Ratio (BCR), and Break Even Point (BEP) for investment evaluation. The financial feasibility of green retrofit items, including solar panels and energy-efficient utilities, is confirmed with an NPV of IDR 140,797,698, IRR of 10.26%, and BCR of 2.21, with feasibility realized in the 17th year. Risk visualization through a Tornado Chart emphasizes the significance of each risk stage on NPV values. In conclusion, the study recommends broader case studies involving multiple certified green mosques for more accurate risk identification. This research provides valuable insights for informed investment decisions in mosque building green items, emphasizing the importance of risk management for long-term sustainability.